The practicalities of establishing a porcine isolated heart model. (July 2018) - Pavey, Warren; Raisis, Anthea; Dunne, Ben; Van Laeken, Els; Jenkinson, Charles; Vincent, Viji; Baird, Peter; Prince, Stuart; Ho, Kwok M.; Merry, Christopher; Gilfillan, Ian
Background: The isolated heart apparatus is over 100 years old, but remains a useful research tool today. While designs of many large animal systems have been described in the literature, trouble-shooting and refining such a model to yield a stable, workable system has not been previously described. This paper outlines the issues, in tabular form, that our group encountered in developing our own porcine isolated heart rig with the aim of assisting other workers in the field planning similar work. The paper also highlights some of the modern applications of the isolated heart apparatus. Methods: Landrace pigs (50-80 kg) were used in a pilot project to develop the model. The model was then used in a study examining the effects of various cardioplegic solutions on function after reanimation of porcine hearts. During the two projects, non-protocol issues were documented as well as their solutions. These were aggregated in this paper. Results: Issues faced by the group without explicit literature solutions included pig size selection, animal acclimatisation, porcine transoesophageal echocardiography, cannulation and phlebotomy for cross-clamping, cardioplegia delivery, heart suspension and rig tuning. Conclusion: Prior recognition of issues and possible solutions faced by workers establishing a porcine isolated heart system will speed progress towards a useable system for research. The isolated heart apparatus remains applicable in transplant, ischaemia reperfusion, heart failure and organ preservation research.